Social work diagnosis conceptualization: Basics social needs - Díaz Herráiz, Eduardo; Fernández de Castro, Patricia (Cuadernos de Trabajo Social, 2013)
Since first social work books, the attempt to define the social diagnosis object has been present. We try to review the social work literature about social diagnosis to propose a systematization and conceptualization that allow to have a social diagnosis conceptual reference, which makes possible homogeneity concepts and categories that are used in Social Work discipline. Four levels of conceptualization are been described about the content of social diagnosis, as approach to four basic social needs categories used as theoretical-analytical reference for any social diagnosis. Therefore, survival and integrity, social inclusion-integration, personal and social autonomy and personal and social identity are taken as conceptual-analytical reference for social diagnosis.
Keywords: Social diagnosis; basics social needs; integrity; inclusion; autonomy; identity